THE EFFECT OF NANOCALCIUM ADDITION FROM SEMBILANG FISH (Paraplotosus albilabris) BONE ON MAKING BISCUITS - Leona Arieska; Desmelati Desmelati; Sumarto Sumarto (Berkala Perikanan Terubuk, 2019)
This study aims to determine the characteristics of biscuit quality with the addition of nanocalcium from the sembilang fish bone (Paraplotosus albilabris). The method used is non factorial completely randomized design with the treatment used in this study, namely the addition of nanocalcium from 4 levels, namely N0 (control: biscuits without the addition of nanocalsium), N1 (addition of 5% nanocalcium), N2 (addition of 10% nanocalsium ), N3 (addition of 15% nanocalcium). The parameters tested were organoleptic and proximate. The results of the study showed that the addition of 15% nanocalcium in Sembilang fish biscuits was the best treatment most panelists liked. Appearance characteristics are brilliant, intact and specific to fish biscuits, non-fishy aroma, and brittle and dense texture, with water content of 5.78%, ash content of 5.10%, fat content of 24.59%, protein content 6.82%, carbohydrate levels 57.71%, phosphorus levels 0.57% and calcium levels 14.14%.